Pharmacoeconomic evaluation of Levothyroxine in the treatment of Hypothyroidism in Nepal (MedS Alliance Journal of Medicine and Medical Sciences, 2023)
INTRODUCTION: Hypothyroidism, is an endocrine disorder, wherein the thyroid gland does not make enough thyroid hormones to meet the body’s needs. Levothyroxine is the mainstay of hormone replacement therapy for hypothyroidism. This study was aimed to evaluate the cost ratio and percentage cost variation, of different brands of levothyroxine, available in the Nepali market.MATERIALS AND METHODS: This observational pharmacoeconomic study was carried out at Department of Pharmacology of Janaki Medical College, Janakpurdham, Nepal from 5 April to 30 May, 2023. Maximum retail price (Cost) in Nepalese currency (NRs), of various brands of levothyroxine available in Nepali market, of same dosage form, strength and number was reviewed for calculating the cost ratio and the percentage cost variation of levothyroxine manufactured by Nepali and Indian Pharmaceutical companies.RESULTS: For 120 tablets of levothyroxine, maximum cost ratio of 1.37 and percentage cost variation of 37.14% was observed with 50 mcg of levothyroxine. For 100 tablets of levothyroxine, maximum cost ratio of 1.65 and percentage cost variation of 65.44% was observed with 50 mcg of levothyroxine.CONCLUSIONS: The findings of this study can be used by a treating physician for prescribing an alternative cheaper brand of levothyroxine for better compliance and for reducing the total health-care cost. Continuous pharmacoeconomic analysis, if carried out at government level, can greatly minimize the cost variation as well as reduce the overall treatment cost for hypothyroid patients in Nepal.